The Effect of Profitability, Financial Leverage, Firm Size, Dividend Policy, and Stock Value on Income Smoothing in Food and Beverages Companies Listed on Indonesia Stock Exchange in 2020-2022 - Sitompul, Rodisna Marselin; Gowon, Muhammad; Jumaili, Salman (International Journal of Multidisciplinary Approach Research and Science, 2024)
Income smoothing is the intentional normalizing of profits to a specified level or trend. Smoothing is an attempt by the company's management to lessen anomalous variations in profitability, to the extent permitted by solid accounting and management standards. This study aims to explore the effects of many factors, including stock value, dividend policy, firm size, profitability, and financial leverage, on income smoothing approaches. The population of the study consisted of the 84 food and beverage companies that were listed on IDX between 2020 and 2022. The sampling process provides 20 companies for a three-year observation period using a purposive sample method. Logistic regression analysis is used in the data analysis process using the SPSS 26 program. The study's findings indicate that income smoothing is influenced by all variables at the same time. Variable dividend policies significantly have effect on income smoothing, partially. However, there is no effect between the factors of stock value, company size, profitability, or leverage.